Da-Yuan-Yin decoction suppresses NETs formation, inhibits the IL-23/JAK2/STAT3 signalling pathway, and modulates metabolic profiles and gut microbiota composition in damp-heat syndrome - Yun Yang; Lengqiu Guo; Jinghua Yu; Wei Peng; Qi Wang; Lan Wei; Xihua Chen; Chunyan Min; Xiaogang Jiang; Song Zhu; Haixin Zhao; Zhenyu Xuan; et al. (Annals of Medicine)
Background Da-Yuan-Yin Decoction (DYY), used since the early Qing Dynasty in China for damp-heat syndrome, was evaluated for its comprehensive protective effects.Materials and methods Rats received a high-fat/high-sugar diet for 14 days, then daily exposure to high temperature/humidity (31.0 ± 0.5°C, 85%-95%) for 10 hours over 14 days. Damp-heat syndrome was induced on day 29 via intraperitoneal lipopolysaccharide (LPS) injections (1 mg/kg and 0.5 mg/kg after 4 hours). Two hours post-modeling, rats received DYY (400 or 800 mg/kg/day) orally for 5 days. Symptoms were scored. On day 33, kidney, spleen, tongue, lung, liver, stomach, and colon tissues underwent histopathological and immunochemical/immunofluorescence analysis. Serum levels of inflammation factors, C-reactive protein (CRP), cell-free DNA (cfDNA), myeloperoxidase (MPO), and superoxide dismutase (SOD) were quantified. Complete blood count (CBC), blood biochemistry, short-chain fatty acids (SCFAs), gut microbiota composition in the colon, and metabolites in the cecum were analyzed.Results DYY significantly reduced symptom scores and decreased CRP level, while also regulating parameters in CBC and biochemical profiles. The treatment ameliorated tissue damage in the kidney, spleen, tongue, lung, liver, stomach, and colon. DYY downregulated citrullinated histone H3 (Cit H3), polyclonal peptidylarginine deiminase 4 (PADI4), and MPO expressions in the lung, stomach, and colon. Furthermore, it modulated inflammatory responses, suppressed the interleukin-23 (IL-23)/janus kinase-2 (JAK2)/signal transduction and transcription activator-3 (STAT3) signaling pathway and enhanced antioxidant activity. DYY administration significantly increased total SCFA content. The intervention restored gut microbiota diversity and abundance, while ameliorating metabolic dysregulation.Conclusion Systemic pathophysiological alterations were observed in rats with damp-heat syndrome. The comprehensive protective effects of DYY involved suppression of neutrophil extracellular traps (NETs) formation through downregulation of PADI4 expression, modulation of inflammatory responses, inhibition of the IL-23/JAK2/STAT3 signaling pathway, restoration of intestinal microecological balance and metabolic homeostasis, and enhancement of antioxidant.